Indivíduo e sociedade no romance Triste fim de Policarpo Quaresma - Oliveira, Irenísia Torres de (2015)
This article analyses the relationships between individual and society in This article analyses the relationship between individual and society in Lima Barreto’s novel The sad end of Policarpo Quaresma, taking into account considerations by Ian Watt and Roberto Schwarz on the realist novel; it investigates initially the constitution of Policarpo as an individual in the novel, from some concrete conditions of relative autonomy and liberty to the ideological combination on which his actions are variedly based (liberal individualism, nationalism and positivist rationalism); it examines also the relationships that situate Policarpo on the ground of concrete life, at each patriotic action, and concludes that the novel proposes an interpretation of a national problem: the inexistence in Brazil of the collective project of a nation.